Phenotypic characterization of antimicrobial drug resistance of Staphylococcus aureus and S. epidermidis strains isolated from various community infections in Oum El Bouaghi city, Algeria - AMINA RAHMANI; LAAREM MERADI; KARIMA MALAWI; FATMA KHANFOUF (Society for Indonesian Biodiversity, 2021)
Abstract. Rahmani A, Meradi L, Malawi K, Khanfouf F. 2021. Phenotypic characterization of antimicrobial drug resistance of Staphylococcus aureus and S. epidermidis strains isolated from various community infections in Oum El Bouaghi city, Algeria. Biodiversitas 22: 2665-2671. In Algeria most community infections caused by Staphylococcus epidermidis and Staphylococcus aureus present resistance to several antibiotics and induce therapeutic failures. The aim of this study is the characterization and the comparison of antimicrobial resistance of Staphylococcus strains isolated from community infection in Oum El Bouaghi city, Algeria. Species identification was realized by conventional biochemical tests and the determination of antibiotics susceptibility pattern was realized by using the agar disk diffusion method, according to the recommendations of the French Society for Microbiology (FSM, 2019). A total of 102 Staphylococci strains were obtained from clinical samples, with a frequency of isolation of 57,8% for S. epidermidis and 42,2% for S. aureus, both strains present a resistance for most used antibiotics, the higher resistance was found for oxacillin in both strains with 25,6% for S. aureus and 42,4% for S. epidermidis. Multidrug-Resistance (MDR) phenotype was detected in 37,3% of S. epidermidis and 14% in S. aureus strains. In Algeria, new control policies should be adopted to prevent the further spread of antimicrobial-resistant strains, especially in the community